Aquatic insects in plateau streams in Southern Brazil: a functional feeding group analysis - Mario Arthur Favretto; Emili Bortolon dos Santos; Osvaldo Onghero-Jr. (Acta Biológica Catarinense, 2023)
Aquatic insects are bioindicators regarding the quality of streams environments. The present study aimed to analyze the community of aquatic insects in streams from the Santa Catarina Plateau, in Brazil. Insects were classified according to their functional trophic structure as gathering-collectors, filtering-collectors, shredders, swallower-predators, perforator-predators and scrapers. Autotrophy and heterotrophy indices were calculated to evaluate the ecological conditions of the sampled streams. Associations between shredders and the riparian vegetation index, filtering-collector index, riverbed stability index, and predator-prey index were performed. The sampled streams demonstrated that the insects inhabiting these environments respond to the strong seasonality observed in the study region, an area located at high altitudes (over 1,200 m a.s.l.) that suffers harsh winters with snow events. This is also reflected in the seasonal heterotrophy and autotrophy index variations noted herein, with higher autotrophy observed during spring and summer. The relationship detected between shredder insects and riparian vegetation indicates that the sampled region may be suffering from deforestation, due to the low contribution of plant matter to the stream waters. However, as many nearby areas are characterized by natural grasslands, it is possible that it is actually an inherent characteristic of the sample area.